Management of capital renewal at machine-building enterprises - N.A. Yefimenko (Економіка, управління та адміністрування)
A unified set of processes for the enrichment forecasting and strategic planning of the enterprises of mechanical restlessness has been proposed based on the algorithm of the functioning of the mechanism for controlling the enrichment renewal process, which is based on the division of the main workers and workers at work places, focusing on activating labor potential, health care provision of a system of rich coordination of individual actions and functions The industrial-state sector of mechanical engineering has a focus on achieving an integral economic effect in material and intellectual production. The model of rich forecasting of the economy has been expanded and implemented, focusing on the specifics of machine-building enterprises based on the parameters of updating the capacity of their capital and the inclusion of dialectical interaction between the two meant: options for strategic directness of machine-building enterprises and informed forecasts of the reaction of the rich medium to these processes. The purpose of this article is to develop the methodology for managing the renewal of capital in machine-building enterprises based on a vicarious storage system. Scientific novelty and practical value. The model of structure formation in a rich creative process has been proposed for the upstream and downstream directions in order to introduce control over the totality of parameters for the renewal of capital in the machine industry. The algorithm was developed for the formation of an integral economic effect of renewing the capital’s capacity, which is based on the very parameters of the generation potential and external officials, which allows us to create a single a system for optimal management of the manufacturing process and to ensure the expansion of the fixed capital renewal of machinery and equipment enterprises by optimizing the strategic management process.